Impact of atmospheric circulation on the occurrence of very strong and extreme cold stress in Poland - Owczarek, Małgorzata; Tomczyk, Arkadiusz M. (Quaestiones Geographicae, 2022)
The primary objective of the study was the determination of the spatial and multiannual variability of occurrence of days with very strong and extreme cold stress in Poland according to the Universal Thermal Climate Index (UTCI), as well as determination of baric conditions favouring their occurrence. The study was based on data from the years 1966/67 to 2018/19 from the Institute of Meteorology and Water Management – National Research Institute and National Centre for Environmental Prediction/National Centre for Atmospheric Research (NCEP/NCAR). The research showed a statistically significant decrease in the number of days with very strong and extreme cold stress on half of the analysed stations, and a slight tendency or no changes on the remaining stations. The occurrence of days with extreme cold stress in Poland, as revealed by the analysis was primarily related to the presence of high-pressure systems blocking zonal circulation. The study resulted in the designation of three circulation types, i.e. two types related to anticyclonic systems and one cyclonic type.